NEW RECORDS AND AN UPDATED CHECKLIST OF AMPHIBIANS (AMPHIBIA) FROM PHU YEN PROVINCE, VIETNAM - Do, Dang Trong; Ngo, Chung Dac; Nguyen, Truong Quang (Hue University Journal of Science: Natural Science, 2017)
Abstract. We herein provide an updated checklist of 33 amphibian species from Phu Yen Province, Vietnam. Eight of them are reported for the first time from this province, namely Ophryophryne gerti, O. hansi, Xenophrys major, Glyphoglossus molossus, Kaloula indochinensis, Microhyla berdmorei, M. nanapollexa, and Amolops spinapectoralis. Additional data of morphological characters of afore mentioned species were also provided. The number of amphibian species recorded was highest from Tay Hoa district (18 species), followed by Song Hinh district (15 species), Dong Xuan district (10 species), Tuy Hoa city (8 specise), Son Hoa district (8 species), Dong Hoa (4 specise), and Tuy An district (3 species). In terms of conservation concern, three species are listed in the IUCN Red List (2016) and one species is listed in the Vietnam Red Data Book (2007).